Self-reported test ordering practices among Canadian internal medicine physicians and trainees: a multicenter cross-sectional survey - Thomas Bodley; Janice L. Kwan; John Matelski; Patrick J. Darragh; Peter Cram (BMC, 2019)
Abstract Background Over-testing is a recognized problem, but clinicians usually lack information about their personal test ordering volumes. In the absence of data, clinicians rely on self-perception to inform their test ordering practices. In this study we explore clinician self-perception of diagnostic test ordering intensity. Methods We conducted a cross-sectional survey of inpatient General Internal Medicine (GIM) attending physicians and trainees at three Canadian teaching hospitals. We collected information about: self-reported test ordering intensity, perception of colleagues test ordering intensity, and importance of clinical utility, patient comfort, and cost when ordering tests. We compared responses of clinicians who self-identified as high vs low utilizers of diagnostic tests, and attending physicians vs trainees. Results Only 15% of inpatient GIM clinicians self-identified as high utilizers of diagnostic tests, while 73% felt that GIM clinicians in aggregate ("others") order too many tests. Survey respondents identified clinical utility as important when choosing to order tests (selected by 94%), followed by patient comfort (48%) and cost (23%). Self-identified low/average utilizers of diagnostic tests were more likely to report considering cost compared to high utilizers (27% vs 5%, P = 0.04). Attending physicians were more likely to consider patient comfort (70% vs 41%, p = 0.01) and cost (42% vs 17%, p = 0.003) than trainees. Conclusions In the absence of data, providers seem to recognize that over investigation is a problem, but few self-identify as being high test utilizers. Moreover, a significant percentage of respondents did not consider cost or patient discomfort when ordering tests. Our findings highlight challenges in reducing over-testing in the current era.